ANALISIS SAMBUNGAN PURUS (TONGUE AND GROOVE JOINTS) PADA DINDING PANEL BETON RINGAN STYROFOAM - Anthony Wisselly; Widodo Kushartomo (JMTS: Jurnal Mitra Teknik Sipil, 2023)
In this research, styrofoam lightweight concrete panel walls were used with dimensions (1000 mm x 500 mm x 60 mm) connected using a purus connection. This connection is used because the setting time is faster and the application is easier than concrete panel joints in general. The tests carried out in this study were flexural strength tests. This test consisted of 2 variations of test objects, including wall panels with 50% and 70% styrofoam usage. Based on the results of the panel wall flexural strength test, 50% styrofoam panel wall joints can withstand loads of up to 560 kg with a maximum deflection of 1,98 mm, while 70% styrofoam panel wall joints can withstand loads of up to 240 kg with a maximum deflection of 0,98 mm. The pattern of damage on panel wall joints styrofoam 50% occurs in the middle of the span then spreads to the side of the panel wall. While on the panel wall joints styrofoam 70% occurred on the side of the panel wall but the connection was not broken. Abstrak Penelitian ini menggunakan dinding panel beton ringan styrofoam dengan ukuran (1000 mm x 500 mm x 60 mm) disambung menggunakan sambungan purus. Sambungan tersebut digunakan karena waktu setting yang lebih cepat dan pengaplikasian yang lebih mudah daripada sambungan panel beton pada umumnya. Pengujian sambungan pada penelitian ini menggunakan metode pengujian kuat lentur. Benda uji terdiri dari 2 variasi, yaitu panel dinding beton yang ditambahkan proporsi styrofoam sebesar 50% dan 70%. Berdasarkan hasil pengujian kuat lentur dinding panel, sambungan dinding panel styrofoam 50% dapat menahan beban hingga 560 kg dengan lendutan maksimal sebesar 1,98 mm, sedangkan sambungan dinding panel panel styrofoam 70% mampu menahan beban hingga 240 kg dengan lendutan maksimal sebesar 0,98 mm. Pola kerusakan pada sambungan dinding panel styrofoam 50% terjadi di tengah bentang kemudian menjalar ke sisi samping dinding panel. Sedangkan pada sambungan dinding panel styrofoam 70% terjadi di sisi samping dinding panel namun sambungan tidak patah.